APLICAÇÃO DE METODOLOGIAS DE TRATAMENTO DE DADOS DO CLIMA LOCAL PARA AVALIAÇÃO DE DIRETRIZES BIOCLIMÁTICAS EM SINOP-MT - Luz, Emília Garcez da; Candido, Cristiane Rossatto; Nogueira, Marta Cristina de Jesus Albuquerque; Santos, Flávia Maria de Moura; Leão, érika Fernanda Toledo Borges (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Knowledge of the climatic conditions to establish requirements for projects depends on meteorological data, which in many cases are not available or are not directed to professionals in the field of construction, requiring a previous statistical treatment for their application. Therefore, the scope of this works was to generate a database for projects for the city of Sinop-MT, located at latitude 11°58'S. For this purpose, data provided by automatic stations were treated and then compiled in climatic files based on the reference year 2007, TRY and CSV, whose missing data were obtained by psychrometric equations. The files were used as input data for plotting the bioclimatic chart, solar chart and wind rose, providing strategies and guidelines for the design of buildings.